Experience of Cyberbullying in Social Media among Polish Muslim Women - Ahmad, Michalina (Annales Universitatis Paedagogicae Cracoviensis | Studia de Cultura, 2025)
The article addresses the issue of cyberbullying towards Polish Muslim women, who experience increased attacks due to their religion. The text presents the results of a survey and in- depth interviews with Polish Muslim women. The analysis aimed to examine how Muslim women relate to the cyberbullying they experience. Does it influence their decisions to engage in online activity or their religiosity? And how do Muslim women see the possibility of changing this unfavourable situation?